2017
DOI: 10.18632/oncotarget.14637
|View full text |Cite
|
Sign up to set email alerts
|

The EMSY threonine 207 phospho-site is required for EMSY-driven suppression of DNA damage repair

Abstract: BRCA1 and BRCA2 are essential for the repair of double-strand DNA breaks, and alterations in these genes are a hallmark of breast and ovarian carcinomas. Other functionally related genes may also play important roles in carcinogenesis. Amplification of EMSY, a putative BRCAness gene, has been suggested to impair DNA damage repair by suppressing BRCA2 function. We employed direct repeat GFP (DR-GFP) and RAD51 foci formation assays to show that EMSY overexpression impairs the repair of damaged DNA, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Instead, overexpression of Akt3 in a genetic model of PDGF-driven murine glioma [ 8 ] or of the clinically relevant activating mutation Akt1-E17K in murine prostate cancer cells facilitated the repair of radiation-induced DNA damage, thereby increasing radiation resistance [ 23 ]. But, Akt can also exert inhibitory actions on the proper repair of DNA damage [ 243 , 141 , 249 ]. In the following paragraphs we highlight current knowledge about important nuclear proteins with suspected regulation by Akt and their positive or negative effect on DNA DSB repair ( Figure 3 ).…”
Section: Subcellular Network Of Akt Target Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, overexpression of Akt3 in a genetic model of PDGF-driven murine glioma [ 8 ] or of the clinically relevant activating mutation Akt1-E17K in murine prostate cancer cells facilitated the repair of radiation-induced DNA damage, thereby increasing radiation resistance [ 23 ]. But, Akt can also exert inhibitory actions on the proper repair of DNA damage [ 243 , 141 , 249 ]. In the following paragraphs we highlight current knowledge about important nuclear proteins with suspected regulation by Akt and their positive or negative effect on DNA DSB repair ( Figure 3 ).…”
Section: Subcellular Network Of Akt Target Proteinsmentioning
confidence: 99%
“…Interestingly, EMSY constitutes another Akt substrate with potential impact on DNA repair if overexpressed [ 249 ]. Breast cancer and ovarian cancer cells show strong amplification of EMSY and this is associated with poor prognosis [ 258 ].…”
Section: Subcellular Network Of Akt Target Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It co-localizes with γH2AX foci, a marker of double-strand breaks, after ionizing irradiation. Overexpression of EMSY elicits a “chromosome instability phenotype” similar to that observed in BRCA2-deficient cells [ 7 , 11 , 41 ]. Consistently, amplification of the EMSY gene has been proposed to mimic the BRCA2 -mutant phenotype which might be a mechanism of BRCA2 pathway inactivation and consequent sensitization of cancer cells to DNA damaging drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, siRNA-mediated silencing of EMSY expression in cell lines with EMSY amplification had no effect on their sensitivity to cisplatin and olaparib. Noteworthy, there is also one recent study that suggested that EMSY participation in DNA repair might be BRCA2-independent [ 41 ]. Considering all these discrepancies, the role of EMSY in DNA repair and cancer therapy still remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%